IDENTIFIKASI PERSEBARAN BAMBU PADA DAERAH ALIRAN SUNGAI PEPE DESA SAWAHAN - Dharmawan Wicaksono; Frista Ananda Rizky; Hasna Khairunnisa; Vania Maharani Rizky Pratiwi; Wahyu Gilang Hermawan (Nusantara Hasana Journal, 2023)
Sawahan Village is one of the villages in Ngemplak District, Boyolali, traversed by a sapling of the Bengawan Solo River, namely the Pepe River. On the riverbanks, most of the area is overgrown with various plants, especially bamboo. Therefore, the location was chosen because it is a location that is overgrown with many bamboo plants and is easy to reach. This study aims to determine the types of bamboo, the distribution of bamboo, and the use of bamboo along the Pepe river flow in Sawahan Village. The method used in this study is a qualitative descriptive method. Meanwhile, the data collection technique is through direct data collection and interviews and with various other secondary data. The results showed that the geographical conditions in the bamboo growth area in the Pepe River flowing in Sawahan Village were irregular, with some regions experiencing erosion on the river's natural embankments. The types of bamboo found in this study are as many as 8, including Gigantochloa apus, Bambusa vulgaris, Dendrocalamus asper, Bambusa blumeana, Gigantochloa atter, Bambusa multiplex, Gigantochloa verticillata, and Dendrocalamus latiflorus Munro. The dominating utilization of bamboo is soil erosion resistance, building construction materials, raw materials for household furniture, livestock pens, bamboo shoots, and bamboo shoot utilization.